Comparative electrophysiology of retinal Müller glial cells—A survey on vertebrate species. Issue 4 (21st October 2016) - Pannicke, Thomas; Chao, T. Ivo; Reisenhofer, Miriam; Francke, Mike; Reichenbach, Andreas
Abstract : Müller cells are the dominant macroglial cells in the retina of all vertebrates. They fulfill a variety of functions important for retinal physiology, among them spatial buffering of K + ions and uptake of glutamate and other neurotransmitters. To this end, Müller cells express inwardly rectifying K + channels and electrogenic glutamate transporters. Moreover, a lot of voltage‐ and ligand‐gated ion channels, aquaporin water channels, and electrogenic transporters are expressed in Müller cells, some of them in a species‐specific manner. For example, voltage‐dependent Na + channels are found exclusively in some but not all mammalian species. Whereas a lot of data exist from amphibians and mammals, the results from other vertebrates are sparse. It is the aim of this review to present a survey on Müller cell electrophysiology covering all classes of vertebrates. The focus is on functional studies, mainly performed using the whole‐cell patch‐clamp technique. However, data about the expression of membrane channels and transporters from immunohistochemistry are also included. Possible functional roles of membrane channels and transporters are discussed. Obviously, electrophysiological properties involved in the main functions of Müller cells developed early in vertebrate evolution. GLIA 2017;65:533–568 Main Points: Müller cells are the dominant macroglia of vertebrate retinae and express a variety of membrane channels, receptors, and transporters. The review gives a survey on electrophysiological properties from Müller cells of all vertebrate classes.